2019
DOI: 10.2337/db19-1817-p
|View full text |Cite
|
Sign up to set email alerts
|

1817-P: Metabolic Surgery Affects Brain Glucose Metabolism, Cognitive Function, and Neuroplasticity in Humans

Abstract: Risk of neurodegenerative disorders, cognitive dysfunction and impaired neuroplasticity (NP) is increased in obesity. We evaluated the effect of metabolic surgery (RYGB) on insulin sensitivity, brain glucose utilization, cognitive function and NP. Thirteen obese subjects (BMI 46±4.9 kg/m2; HbA1c 40.1±5.9 mmol/mol; age 42.4±9.8 years) with no history of psychiatric illness and psychoactive drug use and major brain disorders were recruited. Subjects underwent a 75 gr OGTT during a 60 min FDG dynamic brain PET st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Even though the relevance of our findings under clamp conditions may be criticized because of their experimental nature, systemic insulin levels achieved during euglycemic hyperinsulinemic clamps were those typically seen in the postprandial state. Information about brain glucose metabolism in more physiologic conditions is scanty, but Daniele et al ( 32 ) found that after bariatric surgery, BGU during the oral glucose tolerance test decreased, a finding which is solidly in line with our current findings.…”
Section: Discussionsupporting
confidence: 91%
“…Even though the relevance of our findings under clamp conditions may be criticized because of their experimental nature, systemic insulin levels achieved during euglycemic hyperinsulinemic clamps were those typically seen in the postprandial state. Information about brain glucose metabolism in more physiologic conditions is scanty, but Daniele et al ( 32 ) found that after bariatric surgery, BGU during the oral glucose tolerance test decreased, a finding which is solidly in line with our current findings.…”
Section: Discussionsupporting
confidence: 91%